Analisis Penghargaan Finansial, Pertimbangan Pasar Kerja Dan Persepsi Standar Audit Terhadap Minat Mahasiswa Akuntansi Dalam Pemilihan Karir Menjadi Auditor - Vinolia Supriyati Asyifa; Rukmini Rukmini; Desy Nur Pratiwi (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
A career as an auditor is considered to have good prospects. However, the fact is, the number of accounting graduates each year is not proportional to the growth of auditors in Indonesia. This phenomenon can be a big enough opportunity for graduate accounting students to have a career in the field of auditors. This study aims to determine the effect of financial rewards, labor market considerations, work environment and perceptions of auditing standards on the interest of accounting students in choosing a career as an auditor. This type of research includes quantitative research using primary data obtained from distributing questionnaires. The population in this study were Accounting students of ITB AAS Indonesia with a sample of 86 students determined by purposive sampling technique. The analytical method in this study uses multiple regression analysis statistics. The results of this study are the financial rewards variable and the perception of audit standards have a significant effect on the interest of accounting students in choosing a career to become auditors, while the labor market considerations variable have no significant effect on the interest of accounting students in choosing a career as an auditor.